2022
DOI: 10.1029/2021wr031302
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of Predictability: Identifying Regions of High Precipitation Predictability at Seasonal Timescales From Limited Time Series Observations

Abstract: It is well established that precipitation predictability on seasonal timescales draws upon information about ocean dynamics, which is considered as the principal forcing variable of the atmospheric circulation that ultimately drives regional hydroclimate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…Similarly, precipitation anomalies in Amazonia are found to be associated with Atlantic and Pacific SST anomalies in the tropics [23][24][25] . The patterns of SST anomalies and SSTderived indices in the Pacific are also used for predicting winter precipitation over southern regions of the United States [26][27][28][29] .Multiple lines of evidence indicate that modes of climate variability and associated teleconnections may change by the end of the 21st century 30,31 . For instance, recent studies have shown that the variability of El Niño-Southern Oscillation (ENSO)-driven precipitation is likely to be enhanced over the central-eastern Pacific owing to surface warming, even though change in the strength of ENSO-related SST variability remains uncertain [32][33][34] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, precipitation anomalies in Amazonia are found to be associated with Atlantic and Pacific SST anomalies in the tropics [23][24][25] . The patterns of SST anomalies and SSTderived indices in the Pacific are also used for predicting winter precipitation over southern regions of the United States [26][27][28][29] .Multiple lines of evidence indicate that modes of climate variability and associated teleconnections may change by the end of the 21st century 30,31 . For instance, recent studies have shown that the variability of El Niño-Southern Oscillation (ENSO)-driven precipitation is likely to be enhanced over the central-eastern Pacific owing to surface warming, even though change in the strength of ENSO-related SST variability remains uncertain [32][33][34] .…”
mentioning
confidence: 99%
“…Similarly, precipitation anomalies in Amazonia are found to be associated with Atlantic and Pacific SST anomalies in the tropics [23][24][25] . The patterns of SST anomalies and SSTderived indices in the Pacific are also used for predicting winter precipitation over southern regions of the United States [26][27][28][29] .…”
mentioning
confidence: 99%
“…Accordingly, we used the 3 month average SST data of JFM (January-February-March), FMA (February-March-April), MAM (March-April-May), and AMJ (April-May-June) to predict the occurrence of CDHEs in June, July, August, and September, respectively. All the time series were linearly detrended and this is a general practice (Hari et al 2022, Mamalakis et al 2022) to avoid the influence of long-term trends. For discussion, we divided the Indian mainland into ten sub-regions (figure S5) based on previous studies (Guntu et al 2020, 2023, Guntu and Agarwal 2021).…”
Section: Datamentioning
confidence: 99%
“…However, it is important to note that one of the assumptions of the logistic regression model is the independence of predictors. Therefore, using multiple predictors can lead to overfitting of the prediction model (Mamalakis et al 2022). Overfitting results in reduced generalization performance, especially when predictors are interdependent (Meyer et al 2019).…”
Section: Identification Of Predictorsmentioning
confidence: 99%
See 1 more Smart Citation